Agrotóxicos: uma revisão de suas consequências para a saúde pública - Cassal, Vivian Brusius; Azevedo, Letícia Fátima de; Ferreira, Roger Prestes; Silva, Danúbio Gonçalves da; Simão, Rogers Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study, by means of a review aimed, to report the dangers of indiscriminate use of pesticides and its impact on public health. Objective inspired precisely by the fact that Brazil is among the largest consumers of pesticides in the world and the social and environmental impact caused by the use of these disordered. Thus, know that the risks are not limited to a farmer, reach the springs of water, soil, air, animals, and may also foods marketed in the cities showed toxic waste. Part of agrochemicals has the ability to disperse in the environment, and the other part can accumulate in the human body, bringing various acute and chronic effects. Finally, throughout the world, the effects of environmental impacts are being perceived. In relation to public health, the ever-increasing use of these compounds has caused severe effects, whether acute or chronic, in many workers, especially from rural areas, while other sectors are also affected.